Endocrine effects of hCG supplementation to recombinant FSH throughout controlled ovarian stimulation for IVF: a dose–response study. (1st April 2013) - Thuesen, L. L.; Smitz, J.; Loft, A.; Nyboe Andersen, A.
Summary: Objective: To analyse the endocrine response in relation to the Δ‐4 and Δ‐5 pathways of ovarian steroidogenesis after different doses of human chorionic gonadotrophin (hCG) supplementation to recombinant FSH from Day 1 of controlled ovarian stimulation for IVF. Design: A randomized dose–response pilot study. Patients: A total of 62 IVF patients aged 25–37 years with regular cycles and FSH <12 IU/l were treated with a fixed dose of rFSH 150 IU/day and randomized to four hCG dose groups: Dose 0: 0 IU/day, Dose 50: 50 IU/day, Dose 100: 100 IU/day and Dose 150: 150 IU/day. Results: A significant hCG dose‐dependent incremental increase was found for progesterone (49–160%), 17‐OH‐progesterone (223–614%), androstenedione (91–340%) and testosterone (95–338%) from Dose 0 to Dose 150, respectively. Dehydroepiandrosterone (DHEA) showed minor changes during stimulation and no differences between the groups. The highest oestradiol concentrations were observed in Dose 100 and Dose 150. Sex hormone‐binding globulin (SHBG) increased similarly in all groups at the end of stimulation. No difference was observed for anti‐müllerian hormone (AMH) concentration between the groups, but a 50% decline from the start to the end of the stimulation was found. Conclusion: Supplementation with hCG resulted in a clear dose‐related response for androgens, progesterone and 17‐OH‐progesterone. Oestradiol concentration reached maximum levels with an hCG dose of 100 IU/day, suggesting saturation of aromatase function. No difference between the groups was observed for DHEA, supporting that the stimulatory effects of hCG doses on androgens and oestrogen production were mainly induced via the Δ‐5 pathway. SHBG, being a biomarker of oestrogen/androgen balance, was not changed by increasing hCG.